1998
DOI: 10.1295/polymj.30.43
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Calcium Thiocyanate Solution as a Cellulose Solvent. Structure and Interactions with Cellulose

Abstract: ABSTRACT:Dissolution of cellulose into aqueous (aq) calcium thiocyanate solution was investigated with emphasis on solvent structure and interactions with cellulose. The aq calcium thiocyanate (Ca(SCNh) solution with concentration (CcaT) more than 48.5 wt% could dissolve any celluloses. Solvation measurement revealed that in wt%, the solvent system is formulated by Ca(NCS)2 • xH20 (x 4) + yH 2 0 (y 6), which exhibits mainly non-dissociated thiocyanate with high specific viscosity, as proved by electric conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 16 publications
(9 reference statements)
3
33
0
Order By: Relevance
“…We measured the content of calcium thiocyanate and acetone or methanol in the cellulose gel formed, finding that acetone does not penetrate the system and only extracts calcium thiocyanate and water, while methanol immediately enters the system, extracting calcium thiocyanate and water. 23 These findings imply that methanol destroys the calcium thiocyanate cellulose addition compounds just when the swollen cellulose is immersed in the methanol media. Acetone might gradually decompose the addition compound, restricting the reformation of intra-and inter molecular hydrogen bondings of cellulose, which may lead to lowering the crystallinity of Cell-I comparing with methanol.…”
Section: Structure Of Cellulose Regenerated By Various Reagents Aftermentioning
confidence: 97%
See 1 more Smart Citation
“…We measured the content of calcium thiocyanate and acetone or methanol in the cellulose gel formed, finding that acetone does not penetrate the system and only extracts calcium thiocyanate and water, while methanol immediately enters the system, extracting calcium thiocyanate and water. 23 These findings imply that methanol destroys the calcium thiocyanate cellulose addition compounds just when the swollen cellulose is immersed in the methanol media. Acetone might gradually decompose the addition compound, restricting the reformation of intra-and inter molecular hydrogen bondings of cellulose, which may lead to lowering the crystallinity of Cell-I comparing with methanol.…”
Section: Structure Of Cellulose Regenerated By Various Reagents Aftermentioning
confidence: 97%
“…using IR and NMR, finding that calcium thiocyanate molecules hydrated by less than 4 mol of water form 5-membered cyclic structure with two oxygen atoms of primary alcohol at C(6) position (0(6)) and in a glucopyranose ring (0(5)) in glucose. 16 This situation might influence increase in interplanar spacing of (1 TO) and (II 0) planes by destroying the intramolecular hydrogen bond, such as C(3)0-H · · · 0(5'), as well as intermolecular hydrogen bond C(2)0H · · ·0(6') and C(6)0-H · · · 0(2') in the natural cellulose crystal. The increase in spacings of the both planes may bring about slight decrease in the spacing of the (200) plane, as illustrated in Figure 3.…”
Section: Structural Changes In Wood Pulp Dipped In Aq Calciummentioning
confidence: 99%
“…Figure 6 shows the 13 C-1 H COSY spectrum. Horizontal and longitudinal axes are 13 C and 1 H chemical shifts, respectively and projections on each axis are also shown. Peaks on 2D-spectrum clearly show C-H scalercoupling, indicating correlation between 13 C-1 H peaks.…”
Section: Nm R Spectra Ofcellulose/aq Ca(scn)2 Solution Systemmentioning
confidence: 99%
“…Multihydrate of LiSCN and Ca(SCN) 2 Á4H 2 O showed high solubility of 174 g and 152 g, respectively, in 100 g of ethylenediamine, however, these solutions did not dissolve cellulose at all. It is known that a concentrated Ca(SCN) 2 Á4H 2 O aqueous solution dissolves cellulose above 100 C. 5 Hattori et al 20 also showed that cellulose interacts with Ca(SCN) 2 Á4H 2 O in water at the concentration of 2 was not dissolved in ethylenediamine at 25 C, so that no dissolution of cellulose occurred in the system. Saturated solutions of NaSCN and KSCN in ethylenediamine, i.e., the systems of ethylenediamine/ NaSCN 54/46 (w/w) and ethylenediamine/KSCN 55/45 (w/w) dissolved cellulose (DP210) with high concentrations of 16 and 15 % (w/w), respectively.…”
Section: Resultsmentioning
confidence: 99%